2016
DOI: 10.1016/j.enconman.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on the effects of exhaust locations on energy consumption and thermal environment in an office room served by displacement ventilation

Abstract: 7In an office room, many factors affect the pattern of airflow, thermal comfort, indoor air quality and 8 energy saving. In this study, the effects of the location of exhaust diffusers where the warm and 9 contaminant air is extracted and their relation to room heat sources on thermal comfort and energy 10 saving were investigated numerically for an office served by a displacement ventilation system. The 11 indoor air quality in the breathing level and the inhaled zone were also evaluated. The contaminants 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…It was observed that the parameters such as thermal indoor environment, indoor air quality, thermal comfort and energy savings (up to 25%) were improved through combination of exhaust outlets and room heat sources, such as external walls and lamps. The load on cooling coil was also reduced by 13.8% [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the parameters such as thermal indoor environment, indoor air quality, thermal comfort and energy savings (up to 25%) were improved through combination of exhaust outlets and room heat sources, such as external walls and lamps. The load on cooling coil was also reduced by 13.8% [6].…”
Section: Introductionmentioning
confidence: 99%
“…= concentration of contaminant in exhaust. [8,40] ; normalized concentration C n = C p C e C p = concentration of contaminant in breathing zone; C e = concentration of contaminant in exhaust [8,40].…”
Section: Overall Performance Assessmentmentioning
confidence: 99%
“…The distance between the heat sources and return/exhaust grills is also important to the space cooling load. 22 Specially, when the heat sources (e.g. the lights) are combined with the exhaust grills, the heat sources have little influence on the occupied zone, and therefore it could be reduced as much as 47.7%, as stated in Ahmed et al.…”
Section: Introductionmentioning
confidence: 97%